Restorative Justice Settles Health Disputes Between Patients and Hospitals from an Inclusive Justice Perspective - Mustika, Ni Wayan Eka; Darma, I Made Wirya; Kurniawan, I Gede Agus; Thapa, Nar Yan (Jurnal IUS Kajian Hukum dan Keadilan, 2023)
The legal system in Indonesia has seen significant developments in handling healthcare disputes between patients and hospitals through the introduction of the concept of Restorative Justice. The principles of Restorative Justice and inclusive law can be integrated to create a fair, inclusive resolution of conflicts and repair damaged relationships resulting from these disputes. The objective of this research is to analyze the implementation of Restorative Justice in enhancing the resolution of healthcare disputes between patients and hospitals, considering an inclusive legal framework, and identifying potential major obstacles. The research method used is normative research with a focus on legislative analysis and legal literature to explore the concept of Restorative Justice within an inclusive legal framework for resolving healthcare disputes between patients and hospitals. The researcher employs literature review and document analysis techniques to gather and analyze the legal data required for this research. Implementing Restorative Justice for resolving healthcare disputes between patients and hospitals within an inclusive legal framework is an effective approach for resolving healthcare conflicts. Restorative justice emphasizes relationship restoration and mutual understanding over punishment and can be applied in cases of malpractice, patient dissatisfaction, or violations of medical ethics. To be successful, relevant regulations such as the Arbitration Law in Indonesia, trained mediators, and the involvement of all relevant parties are necessary. Protecting patients' rights, transparency, accountability, and effective communication should also be a focus. By implementing restorative justice and an inclusive legal framework, the resolution of healthcare disputes can be more effective, fair, and can improve the relationship between patients and hospitals